The haunting of Uncle Ron - Fine, Anne (Edinburgh: Barrington Stoke, 2013)
When Uncle Ron comes to visit, he just won't seem to leave! Ian, Mum and Dad don't quite know what do with him - if he's not eating them out of house and home, he's chattering away to the spirits of the dead. But not interesting spirits. All they ever seem to talk about is the colour of doors and what's stuck behind the fridge. So Ian hatches a plan to get rid of Uncle Ron once and for all
Keywords: Children's stories